High-density storage with mobile racks: Picker routing and product location. Issue 3 (14th March 2021) - Foroughi, Amir; Boysen, Nils; Emde, Simon; Schneider, Michael
Abstract: In response to the scarce space in many urban areas, high-density storage has become a widely discussed topic in warehousing research and practice. We investigate a storage setting where mobile racks are mounted on rails, so that a strong engine moves whole blocks of racks aside, opening an aisle and enabling access to a specific rack. Moving the heavy racks takes a considerable amount of time and, consequently, it strongly affects the total pick time. We formalise the resulting operational picker-routing problem, which aims at routing the picker such that as few aisles as possible need to be accessed and the total distance covered is minimal. Moreover, we address the interdependent tactical product-location problem, which deals with deciding on the storage locations of the items to be picked. We present suitable exact and heuristic solution procedures for both problems. In a comprehensive computational study, we apply these algorithms to explore the interdependencies between product location and picker routing, and derive recommendations as to suitable storage policies in a mobile rack warehouse.